COMPARISION OF CLINICAL EFFICACY OF TOPICAL CLINDAMYCIN WITH ADAPALENE AND ADAPALENE ALONE IN TREATMENT OF MILD TO MODERATE FACIAL ACNE VULGARIS - NAGESH BABU REDDY; MEENA K.NANDIMATH (International Journal of Pharma and Bio Sciences, 2013)
Antibiotics are often combined with other agents for topical acne treatments that are effective against inflammatory and non- inflammatory lesions and minimize the development of antibiotic resistance. Retinoids and associated treatments also have anti-inflammatory activity and decrease microcomedon formation. The study was a prospective study done from November 2008 to October 2009. To compare and evaluate the clinical efficacy of topical clindamycin with adapalene and adapalene gel in mild to moderate facial acne vulgaris. Prospective, randomized, open label, comparative-efficacy study was carried out at a Tertiary Care Hospital after obtaining approval from the Institutional Ethics committee to investigate the efficacy and tolerability of adapalene gel 0.1% plus clindamycin phosphate lotion 1%, compared with adapalene 0.1% alone for the treatment of mild to moderate acne vulgaris. A total of 60 patients , divided into two groups, one receiving clindamycin 1% lotion and adapalene 0.1% twice daily (30 patients), while the other group received adapalene gel 0.1% (30 patients) once daily for 12 weeks. A significant reduction of total (P .001), inflammatory (P .004) and non-inflammatory lesions (P .001) was seen in the clindamycin 1% plus adapalene 0.1% group than in the adapalene 0.1% treated group. These significant treatment effects were observed as early as week 4 for both non inflammatory and total lesion counts. The mean percentage reductions were 46.45% versus 25.28% for total lesions, 55.1% versus 44.51% for inflammatory lesions, and 42.8% versus 17.06% for non- inflammatory lesions. The study confirms that the use of adapalene gel 0.1% in combination therapy is beneficial at the initiation of treatment for those suffering from acne.